2009
DOI: 10.1083/jcb.200904001
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila afadin homologue Canoe regulates linkage of the actin cytoskeleton to adherens junctions during apical constriction

Abstract: Cadherin-based adherens junctions (AJs) mediate cell adhesion and regulate cell shape change. The nectin–afadin complex also localizes to AJs and links to the cytoskeleton. Mammalian afadin has been suggested to be essential for adhesion and polarity establishment, but its mechanism of action is unclear. In contrast, Drosophila melanogaster’s afadin homologue Canoe (Cno) has suggested roles in signal transduction during morphogenesis. We completely removed Cno from embryos, testing these hypotheses. Surprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
445
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(486 citation statements)
references
References 74 publications
(138 reference statements)
38
445
3
Order By: Relevance
“…This suggests that other protein(s) stabilize Cno at this location (see below). (Sawyer et al, 2009). Interestingly, we found that Shg was present at the MG and was highly enriched, as is Cno, at the interface between the MG and commissural axons (Fig.…”
Section: Cno Forms a Complex In Vivo With Wrapper And Nrx-ivmentioning
confidence: 69%
“…This suggests that other protein(s) stabilize Cno at this location (see below). (Sawyer et al, 2009). Interestingly, we found that Shg was present at the MG and was highly enriched, as is Cno, at the interface between the MG and commissural axons (Fig.…”
Section: Cno Forms a Complex In Vivo With Wrapper And Nrx-ivmentioning
confidence: 69%
“…Inhibitors of nectin adhesion or afadin knockdown slow the formation of cadherin adhesive clusters in a Ca 2+ -switch assay (Sato et al, 2006;Lorger and Moelling, 2006) or between two cells upon coming into contact with one another (Indra et al, 2014). However, this defect in the kinetics of adherens junction formation does not affect the general appearance of cell-cell adhesion contacts, including the ultrastructural features of adherens junctions (Zhadanov et al, 1999;Sawyer et al, 2009;Tanaka-Okamoto et al, 2011). Therefore, the available data show that nectin facilitates the formation of adherens junctions, but it is involved neither in the basic mechanisms of their assembly nor in their structural organization.…”
Section: Introductionmentioning
confidence: 99%
“…This includes disorganization of the ectoderm, impaired migration of the mesoderm and loss of somites (Ikeda et al, 1999;Zhadanov et al, 1999). In Drosophila, afadin homolog Canoe (Cno) (Miyamoto et al, 1995) is essential during morphogenesis to maintain adherens junctions by connecting adherens junctions to actin (Sawyer et al, 2009). However, in contrast to mammals, Cno is dispensable for cadherin-catenin-based adherens junctions assembly and establishment of cell polarity in the fly (Sawyer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, afadin homolog Canoe (Cno) (Miyamoto et al, 1995) is essential during morphogenesis to maintain adherens junctions by connecting adherens junctions to actin (Sawyer et al, 2009). However, in contrast to mammals, Cno is dispensable for cadherin-catenin-based adherens junctions assembly and establishment of cell polarity in the fly (Sawyer et al, 2009). Cno contributes to regulate signal transduction during morphogenesis and genetically interacts with RAS, JNK, NOTCH and WNT pathways (Miyamoto et al, 1995;Takahashi et al, 1998;Matsuo et al, 1999;Boettner et al, 2003;Carmena et al, 2006).…”
Section: Introductionmentioning
confidence: 99%